Electrochemical device and electronic device including the same

By adding the compound of formula (I) to the electrolyte of the electrochemical device and doping element A into the positive electrode active material, the safety hazards and short cycle life of the electrochemical device during use are solved, and higher safety and stability are achieved.

CN113078362BActive Publication Date: 2025-03-25NINGDE AMPEREX TECHNOLOGY LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202110335485.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2020-03-27
Publication Date
2025-03-25
Estimated Expiration
2040-03-27

AI Technical Summary

Technical Problem

There are safety risks during use of existing electrochemical devices, such as swelling, automatic shutdown and combustion and explosion, and the cycle life is short.

Method used

By adding the compound of formula (I) to the electrolyte and doping element A into the positive electrode active material, the mass ratio of element A and compound of formula (I) is adjusted to form a stable solid electrolyte interface film to reduce side reactions and gas production.

Benefits of technology

It effectively improves the cyclic stability of the electrochemical device, reduces the gas production level, and improves the safety and life of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113078362B_ABST
    Figure CN113078362B_ABST
Patent Text Reader

Abstract

The present application relates to an electrochemical device and an electronic device containing the same. The electrochemical device comprises a positive electrode, a negative electrode, a separator between the positive electrode and the negative electrode, and an electrolyte; wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises an A element, the A element is selected from at least one of Al, B, Ca, Mg, Ti, Cu, Nb, Si, Zr, Y or W, wherein the electrolyte comprises at least one of 1,3-propane sultone or its derivatives, wherein the mass ratio of the element A in the positive electrode active material to the compound of formula (I) is 1:0.2 to 1:50. The electrochemical device described in the present application can exhibit excellent electrochemical performance, especially reducing gas production and improving the cycle stability of the electrochemical device.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] Information about divisional applications

[0002] This case is a divisional application. The parent case of the divisional application is an invention patent application with application date of March 27, 2020, application number 202010232173.1, and invention name “Electrochemical device and electronic device containing the same”. Technical Field

[0003] The present application relates to the field of energy storage technology, and more specifically, to an electrochemical device and an electronic device comprising the same. Background Art

[0004] With the popularization and application of smart products, people's demand for electronic products such as mobile phones, laptops, cameras, etc. has increased year by year, and electrochemical devices as power sources for electronic products play an increasingly important role in our daily lives. Among them, lithium-ion batteries are widely used in smart products, electric vehicles, power tools, drones, intelligent robots, advanced weapons and equipment, and large-scale energy storage due to their advantages such as high energy density, high operating voltage, light weight, low self-discharge rate, long cycle life, no memory effect, and environmental friendliness.

[0005] However, with the widespread application of electrochemical devices in various fields, people have put forward higher requirements for electrochemical devices. For example, people not only require electrochemical devices to have a long service life, but also require to ensure the safety of electrochemical devices. Especially after the frequent occurrence of battery swelling and the automatic shutdown and combustion and explosion of electronic products after a period of use in the market, the market's requirements for the safety of electrochemical devices during use have been raised to a new level. That is, it has become a top priority to develop electrochemical devices with a long service life and high safety. Summary of the invention

[0006] The present application provides an electrochemical device and an electronic device using the electrochemical device, in an attempt to solve at least one problem existing in the related art to at least some extent.

[0007] According to one aspect of the present application, the present application provides an electrochemical device, comprising: a positive electrode; a negative electrode; a separator located between the positive electrode and the negative electrode; and an electrolyte; wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises an A element, and the A element is selected from at least one of Al, B, Ca, Mg, Ti, Cu, Nb, Si, Zr, Y or W, wherein the electrolyte comprises at least one compound of formula (I),

[0008]

[0009] Where R 11 , R 12 , R 13 , R 14 , R 15 , R 16 Each of the above-mentioned elements is independently selected from the group consisting of: H, F, Cl, Br, I, phenyl, substituted or unsubstituted C1-C8 hydrocarbon group, wherein the mass ratio of the element A in the positive electrode active material to the compound of formula (I) is 1:0.2 to 1:50.

[0010] According to an embodiment of the present application, the compound of formula (I) includes at least one of the following:

[0011]

[0012] According to an embodiment of the present application, the electrolyte contains at least one of the compounds of formula (I-1) to (I-7) and the compound of formula (I-8), wherein the total mass ratio of at least one of the compounds of formula (I-1) to (I-7) to the compound of formula (I-8) is greater than 2:1.

[0013] According to an embodiment of the present application, the electrolyte further includes LiPO2F2, and the mass ratio of the element A to the LiPO2F2 is 1:0.01 to 1:20.

[0014] According to an embodiment of the present application, the electrolyte further comprises a compound of formula (II),

[0015]

[0016] Where R 17 is a substituted or unsubstituted C1-C8 alkyl group, p is 0 or 1, and the content of the compound of formula (II) accounts for less than or equal to 20% of the total mass of the electrolyte.

[0017] According to an embodiment of the present application, the electrolyte further includes a first additive, and the first additive includes at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), vinyl sulfate (ES), tris(trimethylsilyl) phosphate (TMSPi), tris(trimethylsilyl) borate (TMSB), triallyl phosphate (TPP), adiponitrile (AND), succinonitrile (SN), 1,3,6-hexanetricarboxylic acid nitrile (HTCN), 1,2,6-hexanetricarboxylic acid nitrile or 1,3,5-pentanetricarboxylic acid nitrile.

[0018] According to an embodiment of the present application, the content of the first additive accounts for 0.1% to 20% of the total mass of the electrolyte.

[0019] According to an embodiment of the present application, the electrolyte further includes a second additive, and the second additive includes at least one of lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium 4,5-dicyano-2-trifluoromethylimidazole (LiTDI), lithium difluorobis(oxalato)phosphate (LiDFOP), lithium difluorooxalatoborate (LiDFOB) or lithium bis(oxalatoborate) (LiBOB).

[0020] According to an embodiment of the present application, the content of the second additive accounts for 0.1% to 5% of the total mass of the electrolyte.

[0021] According to an embodiment of the present application, the positive electrode active material layer includes first particles, wherein the circularity of the first particles is not less than 0.4, and the cross-sectional area of ​​the first particles is not less than 20 μm 2 , based on the total area of ​​the cross section of the positive electrode perpendicular to the current collector, the total cross-sectional area ratio of the first particles is 10% to 50%.

[0022] According to an embodiment of the present application, the first particles include broken particles, and based on the total area of ​​the first particles, the total area of ​​the broken particles is no more than 30%.

[0023] According to an embodiment of the present application, the positive electrode active material layer includes second particles, wherein the circularity of the second particles is less than 0.4, and the cross-sectional area of ​​the second particles is less than 20 μm 2 , based on the total area of ​​the cross-section of the positive electrode perpendicular to the current collector, the total cross-sectional area of ​​the second particles is 10% to 60%.

[0024] In some embodiments, the porosity of the positive electrode is ≤ 25%.

[0025] In some embodiments, based on the cross-sectional area of ​​the positive electrode perpendicular to the current collector, the cross-sectional area of ​​the positive electrode current collector accounts for 5% to 20%.

[0026] According to an embodiment of the present application, the positive electrode active material includes at least one of the compound of formula III or the compound of formula IV:

[0027] Li n Ni 1-a-b-c Co a Mn b A c O 2-m D m(Formula III)

[0028] Among them, 0.90≤n≤1.10, 0.05≤a≤0.3, 0.002≤b≤0.3, 0.001≤c≤0.1, 0≤m≤0.05, and 0.60<1-bc<0.95;

[0029] LiCoA e O 2-f D f (Formula IV)

[0030] Where 0.001≤e≤0.1, 0≤f≤0.1,

[0031] Wherein D is selected from at least one of S, F, N, Cl or I.

[0032] According to an embodiment of the present application, the isolation film includes a substrate layer and a surface treatment layer, the surface treatment layer includes inorganic ceramic particles, and a thickness ratio of the substrate layer to the surface treatment layer is 2:1 to 20:1.

[0033] According to one aspect of the present application, the present application provides an electronic device, which includes the electrochemical device according to the present application.

[0034] In at least one aspect, the present application can effectively improve the cycle stability of the electrochemical device and effectively reduce the gas generation level of the electrochemical device by adding the compound of formula (I) to the electrolyte, doping the element A in the positive electrode active material, and adjusting the mass ratio of the element A in the positive electrode active material to the compound of formula (I).

[0035] Additional aspects and advantages of the present application will be described, shown, or explained in part in the subsequent description through implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The following will briefly describe the drawings necessary for describing the embodiments of the present application or the prior art to facilitate the description of the embodiments of the present application. Obviously, the drawings described below are only some of the embodiments in the present application. For those skilled in the art, without the need for creative work, drawings of other embodiments can still be obtained based on the structures illustrated in these drawings.

[0037] Figure 1A and Figure 1B The morphologies of polycrystalline positive electrode active materials and quasi-single crystal positive electrode active materials are shown respectively. DETAILED DESCRIPTION

[0038] The embodiments of the present application will be described in detail below. In the full text of the present application specification, the same or similar components and components with the same or similar functions are represented by similar reference numerals. The embodiments of the accompanying drawings described herein are illustrative, graphical, and are used to provide a basic understanding of the present application. The embodiments of the present application should not be interpreted as limiting the present application.

[0039] As used herein, the term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs exactly as well as an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. For example, if the difference between two numerical values ​​is less than or equal to ±10% of the average value of the values ​​(e.g., less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%), then the two numerical values ​​can be considered to be "about" the same.

[0040] In addition, sometimes amounts, ratios and other numerical values ​​are presented in range format herein. It should be understood that such range format is for convenience and brevity, and should be flexibly understood to include not only the numerical values ​​explicitly specified as range limits, but also all individual numerical values ​​or sub-ranges encompassed within the range, as if each numerical value and sub-range were explicitly specified.

[0041] In the detailed description and claims, a list of items connected by the terms "one or more of," "one or more of," "one or more of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.

[0042] The term "circularity" refers to the degree to which the cross section of a particle is close to a theoretical circle. Circularity R = (4π × area) / (circumference × circumference), when R is 1, the shape is a circle; the smaller R is, the more irregular the shape is, and the greater the difference from a circle. This application uses a roundness meter to measure the circularity of the positive electrode active material particles. The specific test method can be found in the following specific embodiments.

[0043] The term "broken particles" refers to continuous lines with a length of not less than 0.1 μm and a width of not less than 0.01 μm in the cross section of the particles in the image under a scanning electron microscope, which are regarded as cracks, and particles with cracks are regarded as broken particles.

[0044] The term "hydrocarbon group" refers to a group containing C and H elements. For example, the hydrocarbon group may include alkyl, alkenyl, alkynyl and aryl. Among them, the hydrocarbon group includes straight chain and branched hydrocarbon groups. For example, the hydrocarbon group may be C1-C 50 Hydrocarbon, C1-C 40 Hydrocarbon, C1-C 30 Hydrocarbon, C1-C 20 Hydrocarbon, C1-C 12 Hydrocarbon, C1-C 10 Hydrocarbyl, C1-C8 hydrocarbyl, C1-C6 hydrocarbyl, C2-C6 hydrocarbyl, C2-C5 hydrocarbyl. In addition, the hydrocarbyl group may be optionally substituted.

[0045] The term "alkyl" encompasses both straight and branched chain alkyl groups. For example, an alkyl group may be C1-C 50 Alkyl, C1-C 40 Alkyl, C1-C 30 Alkyl, C1-C 20 Alkyl, C1-C 12 Alkyl, C1-C 10 In some embodiments, the alkyl group includes methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, hexyl, heptyl, octyl, etc. In addition, the alkyl group can be optionally substituted.

[0046] When the above groups are substituted, the substituents may be independently selected from a silane group, a siloxane group, an amino group, an ether group, an ester group, a carboxyl group, a sulfonic acid group, a mercapto group, a cyano group, a halogen group or a combination thereof.

[0047] 1. Electrochemical Device

[0048] When an electrochemical device is left alone in a high temperature environment or during the charge and discharge cycle, it will produce gas, causing the electrochemical device to swell. When the gas production phenomenon is serious, it will affect the safety of electronic products, thus giving consumers a negative experience and even threatening consumers' personal safety. Therefore, one of the key factors to improve the safety of electrochemical devices is to reduce the gas production of electrochemical devices.

[0049] The present application finds that the main reason for the gas production phenomenon in the electrochemical device is that side reactions occur between the electrolyte and the positive electrode active material and the negative electrode active material to generate gas byproducts. In addition, the present application also finds that in the process of cold pressing the positive electrode sheet and charging and discharging the electrochemical device, the positive electrode active material particles are prone to breakage, and after the particles are broken, new interfaces are exposed, causing the electrolyte to penetrate into the interior of the particles through the cracks and react with the positive electrode active material at the new interface, aggravating the occurrence of gas production and causing the capacity of the electrochemical device to decay rapidly as the charge and discharge cycle proceeds. In addition, during the charging process of the electrochemical device, as lithium ions are continuously released from the positive electrode active material, the binding force between the active metal (for example, nickel or cobalt) in the positive electrode active material and oxygen is weakened, oxygen is released, and the released oxygen oxidizes the electrolyte, aggravating gas production.

[0050] At least based on the above-mentioned research on the gas production phenomenon, the present application has improved the electrolyte system and the positive electrode active material at the same time, and is committed to the research on the matching relationship between the electrolyte system and the positive electrode active material, giving full play to the synergistic effect between the electrolyte system and the positive electrode active material, so as to obtain an electrochemical device with low gas production and good cycle performance.

[0051] In some embodiments of the present application, the present application provides an electrochemical device comprising: a positive electrode; a negative electrode; a separator located between the positive electrode and the negative electrode; and an electrolyte; wherein the positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises an A element, the A element comprises or is selected from at least one of Al, B, Ca, Mg, Ti, Cu, Nb, Si, Zr, Y or W, wherein the electrolyte comprises at least one compound of formula (I),

[0052]

[0053] Where R 11 , R 12 , R 13 , R 14 , R 15 , R 16Each of the above-mentioned elements is independently selected from the group consisting of: H, F, Cl, Br, I, phenyl, substituted or unsubstituted C1-C8 hydrocarbon group, wherein the mass ratio of the element A in the positive electrode active material to the compound of formula (I) is 1:0.2 to 1:50.

[0054] The compound of formula (I) is at least one of 1,3-propane sultone or its derivatives. The compound of formula (I) is added to the electrolyte as an additive to form a stable solid electrolyte interface film (SEI film) on the surface of the positive electrode active material particles, thereby reducing the side reaction between the positive electrode active material and the electrolyte. Doping or coating the A element in the positive electrode active material can, on the one hand, improve the structural stability of the material itself and reduce oxygen release, and on the other hand, can cooperate with the compound of formula (I) to stabilize the surface of the positive electrode active material particles and reduce the occurrence of side reactions.

[0055] In addition, by adjusting the mass ratio between the element A in the positive electrode active material and the compound of formula (I), not only can the rapid increase of impedance in the early stage of the cycle be suppressed and the cycle capacity loss be reduced, but also the gas generation problem caused by material breakage in the late stage of the cycle can be improved. When the mass ratio of the element A in the positive electrode active material to the compound of formula (I) is 1:0.2 to 1:50, the electrochemical device can be promoted to exert excellent electrochemical performance.

[0056] When the amount of the compound of formula (I) added is too much compared to the doped or coated element A, in the early stage of the charge and discharge cycle, there will be an excessive amount of the compound of formula (I) participating in the formation of the SEI film, which may cause the SEI film to be too thick. Although the SEI film helps to protect the positive electrode active material, an overly thick SEI film will lead to a rapid increase in the charge transfer impedance at the surface of the positive electrode active material and cause a loss of cycle capacity. When the amount of the compound of formula (I) added is too small compared to the doped or coated element A, in the late stage of the charge and discharge cycle, when the positive electrode active material particles are broken, the content of the compound of formula (I) in the electrolyte may not be sufficient to participate in the formation of the SEI film at the new interface, making it difficult to improve the cycle stability of the electrochemical device in the late stage of the cycle and to suppress gas production.

[0057] As a non-limiting example, the compound of formula (I) includes or is selected from at least one of the following:

[0058]

[0059] In some embodiments, the electrolyte contains both 1,3-propane sultone (i.e., a compound of formula (I-8)) and at least one derivative of 1,3-propane sultone. In some embodiments, the derivative of 1,3-propane sultone includes or is selected from at least one of the compounds of formula (I-1) to formula (I-7).

[0060] The derivatives of 1,3-propane sultone are used to change the SEI film composition by adding substituents while maintaining the overall structure of the organic molecule unchanged, thereby reducing the amount of 1,3-propane sultone used without substantially reducing the cycle stability of the electrochemical device and increasing the gas production. In some embodiments, in the electrolyte, the mass ratio of the added 1,3-propane sultone derivative to 1,3-propane sultone is greater than 2:1. In some embodiments, in the electrolyte, the total weight of at least one of the compounds of formula (I-1) to formula (I-7) to the mass ratio of the compound of formula (I-8) is greater than 2:1. The mass ratio within this range can reduce the amount of 1,3-propane sultone used while maintaining the cycle stability of the electrochemical device.

[0061] In some embodiments, the electrolyte further includes lithium difluorophosphate (LiPO2F2), and the mass ratio of the element A in the positive electrode active material to the LiPO2F2 is 1:0.01 to 1:20. The addition of LiPO2F2 can further improve the cycle stability of the electrochemical device, which is specifically manifested in that the addition of LiPO2F2 can increase the LiF component in the SEI film, thereby enhancing the stability of the SEI film and further reducing the occurrence of side reactions. In addition, by adjusting the mass ratio of the element A in the positive electrode active material to the LiPO2F2 in the range of 1:0.01 to 1:20, it is possible to promote LiPO2F2 to play a better role, avoid the element A from being attacked by HF in the electrolyte, and at the same time, it will not increase the impedance value of the positive electrode surface.

[0062] In some embodiments, the electrolyte further comprises a compound of formula (II), wherein R 17 is a substituted or unsubstituted C1-C8 alkyl group, p is 0 or 1,

[0063]

[0064] The addition of the compound of formula (II) can reduce the migration impedance of lithium ions during the charge and discharge process of the electrochemical device, and improve the room temperature cycle performance, rate performance and discharge performance of the electrochemical device in a low temperature environment.

[0065] In some embodiments, the compound of formula (II) may include at least one of the following:

[0066]

[0067] However, the reaction activity of the compound of formula (II) is relatively high, and it will destroy the SEI film formed on the surface of the positive electrode active material particles. Especially in the later stage of the charge and discharge cycle, the continuous destruction of the SEI film by the compound of formula (II) will aggravate gas production and reduce the cycle stability of the electrochemical device. Therefore, controlling the content of the compound of formula (II) within a certain range can improve the cycle stability of the electrochemical device, reduce gas production, and take into account the rate performance and low temperature performance of the electrochemical device. In some embodiments, the content of the compound of formula (II) accounts for less than or equal to 20% of the total mass of the electrolyte. In some embodiments, the content of the compound of formula (II) accounts for less than or equal to 15% of the total mass of the electrolyte.

[0068] In some embodiments, the compound of formula (II) may be derived from the decomposition product of diethyl carbonate, propyl propionate, ethyl propionate, and propyl acetate.

[0069] In some embodiments, the electrolyte further includes a first additive, which includes or is selected from at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, adiponitrile, succinonitrile, 1,3,6-hexanetricarboxylic acid nitrile, 1,2,6-hexanetricarboxylic acid nitrile or 1,3,5-pentanetricarboxylic acid nitrile.

[0070] In some embodiments, based on the total mass of the electrolyte, the content of the first additive is 0.01% to 30%, 0.01% to 20%, 0.01% to 10%, 0.01% to 5%, 0.1% to 30%, 0.1% to 20%, 0.1% to 10%, 0.1% to 5%, 1% to 30%, 1% to 20%, 1% to 10% or 1% to 5%.

[0071] In some embodiments, the electrolyte further includes a second additive, which includes or is selected from at least one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium 4,5-dicyano-2-trifluoromethylimidazole, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate, or lithium bis(oxalatoborate).

[0072] In some embodiments, based on the total mass of the electrolyte, the content of the second additive is 0.01% to 20%, 0.01% to 10%, 0.01% to 5%, 0.01% to 3%, 0.1% to 20%, 0.1% to 10%, 0.1% to 5%, 0.1% to 3%, 1% to 20%, 1% to 10%, 1% to 5% or 1% to 3%.

[0073] The above-mentioned first additive and second additive of the present application have a higher reduction potential or a lower oxidation potential, which can form a SEI film on the surface of the positive electrode active material in priority to the compound of formula I and the compound of formula II, reduce the side reaction between the electrolyte and the surface of the positive electrode active material, thereby improving the cycle stability of the electrochemical device in the early stage of the cycle and reducing gas production. At the same time, the addition of the first additive and the second additive can also reduce the consumption of the compound of formula I in the formation stage and the early stage of the cycle, ensuring that the compound of formula I forms a stable SEI film at the new interface formed at the rupture of the positive electrode active material particles in the late stage of the cycle, providing a guarantee for the electrochemical stability of the electrochemical device in the late stage of the cycle.

[0074] In some embodiments, in the process of preparing the positive electrode active material particles into a positive electrode, it is necessary to use a cold pressing process to press the positive electrode active material particles tightly together to increase the compaction density of the positive electrode active material layer, thereby reducing the direct current resistance (DCR) of the electrochemical device. In addition, the above-mentioned cold pressing process will also press the positive electrode active material layer and the positive electrode current collector tightly together to prevent the separation between the positive electrode active material layer and the positive electrode current collector during the charging and discharging process of the electrochemical device. However, when the pressure used in the cold pressing process is greater, the compaction density in the positive electrode active material layer is also greater, and the positive electrode active material particles are easier to break. In addition, the process of charging and discharging the electrochemical device is the process of lithium ions being embedded and extracted in the positive electrode active material particles, which is accompanied by a drastic volume change of the positive electrode active material particles, thereby causing the particles to break.

[0075] In order to reduce the degree of breakage of the positive electrode active material during the cold pressing stage of electrode preparation and the charging and discharging process of the electrochemical device, the present application uses a mixture of positive electrode active materials with different particle sizes as the positive electrode active material, wherein the positive electrode active material particles have different roundness and cross-sectional areas. By matching large and small particles, not only can the compaction density of the positive electrode be improved, but also the breakage of the positive electrode active material during the cold pressing stage and the cycle process can be reduced, thereby improving the cycle performance of the electrochemical device and reducing gas production.

[0076] In some embodiments, the positive electrode active material layer includes first particles, the circularity of the first particles is not less than 0.4, and the cross-sectional area of ​​the first particles is not less than 20 μm 2 .

[0077] In some embodiments, the first particle is a polycrystalline particle. A polycrystalline particle is a collection of a plurality of single crystal particles, wherein a single crystal is a crystal in which particles are regularly and periodically arranged in three-dimensional space. Figure 1A As shown, the morphology of the polycrystalline particles is spherical or ellipsoidal, with a large roundness and a large cross-sectional area.

[0078] Compared with small-sized particles, large-sized particles are more likely to break during cold pressing and during the charge and discharge process of the electrochemical device. In some embodiments, by reducing the content of large-sized particles in the positive electrode active material, the degree of breakage can be effectively alleviated, thereby reducing the occurrence of side reactions. In some embodiments, based on the total area of ​​the cross section of the positive electrode perpendicular to the current collector, the total cross-sectional area of ​​the first particle accounts for 10% to 50%.

[0079] In some embodiments, the first particles include broken particles, and the total area of ​​the broken particles is no more than 30%, no more than 28%, no more than 24%, no more than 20%, no more than 18%, no more than 15%, no more than 10%, or no more than 5%, based on the total area of ​​the first particles in the cross section of the positive electrode active material layer. In some embodiments, when the discharge capacity of the electrochemical device decays to 80% to 90% of the initial discharge capacity, the total area of ​​the broken particles is no more than 20%, no more than 15%, no more than 10%, or no more than 5%, based on the total area of ​​the first particles in the cross section of the positive electrode active material layer.

[0080] In some embodiments, the positive electrode active material layer includes second particles, the circularity of the second particles is less than 0.4, and the cross-sectional area of ​​the second particles is less than 20 μm 2 .

[0081] In some embodiments, the second particles include quasi-single crystal particles. The quasi-single crystal particles are a collection of single crystals with a smaller number but larger grain size. Figure 1B As shown, the morphology of the single-crystal-like particle B is irregular, its circularity is small, and its cross-sectional area is small.

[0082] The addition of the second particles can effectively reduce the degree of breakage of the first particles. This is specifically manifested in that the second particles have irregular morphology and small particle size, and can be filled between multiple first particles to play a good buffering role, reducing the rigid collision between the first particles, thereby reducing the degree of breakage of the first particles and the occurrence of side reactions. In some embodiments, based on the total area of ​​the cross section of the positive electrode perpendicular to the current collector, the total cross-sectional area of ​​the second particles accounts for 10% to 60%.

[0083] In some embodiments, the porosity of the positive electrode is ≤ 25%.

[0084] In some embodiments, the cross-sectional area of ​​the positive electrode current collector is calculated based on the cross-sectional area of ​​the positive electrode perpendicular to the current collector, and the cross-sectional area accounts for 5% to 20%. In some embodiments, the positive electrode active material described in the present application includes lithium, at least one active metal and element A, wherein the active metal element includes or is selected from at least one of the following elements: cobalt (Co), nickel (Ni), manganese (Mn), magnesium (Mg), aluminum (Al), boron (B), titanium (Ti), vanadium (V), chromium (Cr), iron (Fe), copper (Cu), zinc (Zn), molybdenum (Mo), tin (Sn), calcium (Ca), strontium (Sr), tungsten (W), yttrium (Y), lanthanum (La) and zirconium (Zr). The specific types of positive electrode active materials described in the present application are not subject to specific restrictions and can be selected according to needs.

[0085] In some embodiments, the positive electrode active material described in the present application includes a ternary material. The term "ternary material" refers to a ternary material known in the art, such as the ternary material recorded in "Ternary Materials for Lithium Ion Batteries - Process Technology and Production Application" (Wang Weidong, Qiu Weihua, Ding Qianqian, etc., Chemical Industry Press, May 2015). In some embodiments, the ternary material described in the present application includes lithium nickel cobalt manganese oxide.

[0086] In some embodiments, the positive electrode active material described herein includes the following compound of formula III:

[0087] Li n Ni 1-a-b-c Co a Mn b A c O 2-m D m (Formula III)

[0088] wherein 0.90≤n≤1.10, 0.05≤a≤0.3, 0.002≤b≤0.3, 0.001≤c≤0.1, 0≤m≤0.05, and 0.60<1-bc<0.95; and wherein element D includes or is selected from at least one of S, F, N, Cl or I.

[0089] In some embodiments, the cathode active material described herein includes lithium cobalt oxide. In some embodiments, the cathode active material described herein includes the following formula IV compound:

[0090] LiCoA e O 2-f D f (Formula IV)

[0091] Wherein 0.001≤e≤0.1, 0≤f≤0.1, and wherein element D includes or is selected from at least one of S, F, N, Cl or I.

[0092] The positive electrode current collector may be a common positive electrode current collector in the art, and in some embodiments, includes, but is not limited to, aluminum foil or nickel foil.

[0093] In some embodiments, in addition to the positive electrode active material described herein, the positive electrode active material layer further comprises a binder and a conductive agent.

[0094] The binder can not only improve the bonding between the positive electrode active material particles, but also improve the bonding between the positive electrode active material and the positive electrode current collector. In some embodiments, non-limiting examples of binders include polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylic (ester) styrene-butadiene rubber, epoxy resin, nylon, etc. In some embodiments of the present application, the content of the binder is in the range of 1% to 5% based on the total mass of the positive electrode active material layer. In some embodiments of the present application, the content of the binder is in the range of 1.25% to 5% based on the total mass of the positive electrode active material layer.

[0095] Conductive agent can be used to enhance the conductivity of electrode. The present application can adopt any conductive material as conductive agent, as long as the conductive material does not cause unwanted chemical changes. In certain embodiments, non-limiting examples of conductive materials include carbon-based materials (e.g., natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, carbon fiber, etc.), metal-based materials (e.g., metal powder, metal fiber, etc., including, for example, copper, nickel, aluminum, silver, etc.), conductive polymers (e.g., polyphenylene derivatives) and mixtures thereof, etc.

[0096] In some embodiments, the electrochemical device described in the present application further comprises a negative electrode, wherein the negative electrode comprises a negative electrode active material layer and a negative electrode current collector, and the negative electrode active material layer comprises the negative electrode active material described in the present application. The negative electrode active material is capable of reversibly embedding and extracting lithium ions. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material may include or be selected from one or more of the following materials: carbonaceous materials, siliceous materials, alloy-based materials, composite oxide materials containing lithium metal, and the like. In some embodiments, non-limiting examples of carbonaceous materials include crystalline carbon, amorphous carbon, and mixtures thereof. Crystalline carbon may be amorphous or flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, and the like.

[0097] In some embodiments, examples of the negative electrode active material may include, but are not limited to, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB for short), hard carbon, soft carbon, silicon, silicon-carbon composites, Li-Sn alloys, Li-Sn-O alloys, Sn, SnO, SnO2, spinel-structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy.

[0098] In some embodiments, the negative electrode current collector may be a commonly used negative electrode current collector in the art, including, but not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and combinations thereof.

[0099] In some embodiments, in addition to the negative electrode active material, the negative electrode active material layer described in the present application further includes a binder and a conductive agent. The binder and conductive agent in the negative electrode can be made of the same materials as described above, and no further details are given here.

[0100] In some embodiments, the electrochemical device of the present application further comprises a separator disposed between the positive electrode and the negative electrode to prevent short circuit. The present application has no particular restrictions on the material and shape of the separator used in the electrochemical device, which may be any material and shape disclosed in the prior art. In some embodiments, the separator comprises a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.

[0101] In some embodiments, the isolation film includes a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film with a porous structure. In some embodiments, the material of the substrate layer may include or be selected from at least one of polyethylene, polypropylene, polyethylene terephthalate or polyimide. Specifically, polyethylene porous film, polypropylene porous film, polyethylene non-woven fabric, polypropylene non-woven fabric or polypropylene-polyethylene-polypropylene porous composite film etc. may be selected.

[0102] In some embodiments, the surface treatment layer may be, but is not limited to, a polymer layer, an inorganic layer, or a hybrid layer formed of a polymer and an inorganic layer.

[0103] The inorganic layer may include inorganic ceramic particles. In some embodiments, the inorganic ceramic particles may include or be selected from one or a combination of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate.

[0104] In some embodiments, the inorganic layer further comprises a binder. In some embodiments, the binder may comprise or be selected from one or a combination of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene.

[0105] In some embodiments, the polymer layer may include a polymer. In some embodiments, the polymer material may include or be selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene).

[0106] In some embodiments, the thickness ratio of the substrate layer to the surface treatment layer is 2:1 to 50:1, 2:1 to 40:1, 2:1 to 30:1, or 2:1 to 20:1.

[0107] It will be understood by those skilled in the art that the electrochemical device of the present application may be a lithium ion battery or any other suitable electrochemical device. Without departing from the disclosure of the present application, the electrochemical device in the embodiments of the present application includes any device in which an electrochemical reaction occurs, and its specific examples include all kinds of primary batteries, secondary batteries, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery.

[0108] The purpose of the electrochemical device of the present application is not particularly limited, and it can be used for any purpose known in the prior art. According to some embodiments of the present application, the electrochemical device of the present application can be used in electronic devices, wherein the electronic device includes, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, a liquid crystal television, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.

[0109] The technical solution of the present invention is further described below by taking lithium ion batteries as an example and combining comparative examples and embodiments, but is not limited thereto. Those skilled in the art will understand that the preparation method described in this application is only an exemplary embodiment, and any modification or replacement of the technical solution of the present invention without departing from the scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0110] Example

[0111] Preparation of lithium-ion batteries

[0112] The positive electrode active materials in the examples and comparative examples were prepared into lithium-ion full batteries using the following preparation method.

[0113] (1) Preparation of positive electrode: The positive electrode active material prepared in the following examples and comparative examples, the conductive agent Super P, and polyvinylidene fluoride (PVDF) were thoroughly stirred and mixed in N-methylpyrrolidone at a weight ratio of 97.7:1.3:1.0 to prepare a positive electrode slurry; the obtained positive electrode slurry was then evenly coated on the positive electrode current collector aluminum foil, and then dried at 85°C to obtain a positive electrode active material layer, and then cold pressed, slit, cut to pieces, and welded to the positive electrode ears to obtain a positive electrode.

[0114] (2) Preparation of negative electrode: artificial graphite, sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) are mixed in deionized water at a weight ratio of 97:1:2 and stirred to form a negative electrode slurry; the negative electrode slurry is then evenly coated on the negative electrode current collector copper foil, and then dried at 85°C to form a negative electrode active material layer, and then cold pressed, slit, cut, and welded to the negative electrode tab to obtain the negative electrode.

[0115] (3) Preparation of electrolyte: In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC) and diethyl carbonate (DEC) were mixed in a mass ratio of 15:25:60, and then additives were added. After dissolving and stirring, lithium salt LiPF6 was added and mixed to obtain an electrolyte. The concentration of LiPF6 was 1.20 mol / L. The specific types and contents of the additives used in the electrolyte are shown in Tables 1 to 3.

[0116] (4) Preparation of isolation membrane: 9 μm thick polyethylene (PE) was selected as the isolation membrane, and inorganic particles (the mass ratio of flaky boehmite and Al2O3 was 70:30) were evenly dispersed in polyvinylidene fluoride (PVDF) to obtain a slurry. The slurry was coated on the front and back sides of the isolation membrane respectively, and the isolation membrane was obtained after drying. The total thickness of the coating was 3 μm.

[0117] (5) Assembly of lithium-ion batteries: stack the positive electrode, separator, and negative electrode in order, with the separator between the positive and negative electrodes to play an isolating role, then wind them, weld the tabs to obtain a bare cell, place the bare cell in an outer packaging foil aluminum-plastic film, inject the prepared electrolyte, and undergo vacuum packaging, standing, formation, shaping, capacity testing and other processes to obtain a soft-pack lithium-ion battery.

[0118] Test methods for electrolyte quality

[0119] Discharge the battery at a constant current of 0.1C to 2.8V, weigh the battery and calculate it as m0, then disassemble the battery, quickly extract the bare battery core and the outer foil aluminum plastic film obtained by disassembly into high-purity acetonitrile (purity ≥ 99.9%), take the extracted clear liquid to test the gas chromatography, and obtain the relative content of each component in the electrolyte. Dry the extracted bare battery core and the outer foil aluminum plastic in a vacuum oven, weigh the total mass and calculate it as m1. The actual mass of each component in the battery is the product of (m0-m1) and the relative content of each component.

[0120] Test method for element A content in positive electrode

[0121] Take out the positive electrode from the bare cell dried in the above electrolyte quality test, weigh the disassembled positive electrode and calculate the mass as m2, select the area coated with positive electrode active material on both sides to punch into small discs with a diameter of 18 mm and weigh them as m3, take 10 small discs and dissolve them completely with aqua regia, then vacuum filter, wash with 20 mL of pure water, repeat this step twice to obtain the filtrate, and then transfer it to a volumetric flask to 100 mL, and use inductively coupled plasma ICP to use the standard curve method to test the concentration of element A to be c0 (mg / L). According to the thickness and length of the positive electrode used, the total mass of the substrate in the positive electrode is calculated to be m4, and the mass of the positive current collector corresponding to the small disc with a diameter of 18 mm is m5. The mass of element A in the battery is c0×100×(m2-m4) / (m3-m5);

[0122] For a positive electrode with a single-sided coating of positive electrode active material, the mass of active material per unit area is calculated as half of the weight of the positive electrode active material in the double-sided coating area.

[0123] Test of cross-sectional area and cross-sectional area ratio of positive electrode active material particles

[0124] Use an ion polisher (model: JEOL-IB-09010CP) to cut the positive electrode perpendicular to the positive current collector to obtain a cross section. Use a scanning electron microscope to observe the above cross section at an appropriate magnification, use the backscatter mode to take pictures, use the Image J software to identify the graphic morphology function to identify particles A, broken particles in particles A, and current collectors, and calculate their respective corresponding areas accordingly. The total area of ​​the cross section of the positive electrode sheet is S, the total area of ​​particles A is S1 (including broken particles), the total area of ​​broken particles in particles A is S2, the area of ​​the positive current collector is S3, the porosity is P, and the area share of the conductive agent and bonding is ignored. In this application, the circularity of particle A is greater than or equal to 0.4, and the cross-sectional area of ​​a single particle A is greater than or equal to 20μm 2 .

[0125] Total area proportion of particle A = S1 / S×100%;

[0126] The total area ratio of broken particles in particle A = S2 / S×100%;

[0127] The total area of ​​the broken particles accounts for the total area of ​​particle A = S2 / S1×100%;

[0128] The total area proportion of particle B = (S-S1–S3) / S×100%-P.

[0129] Thickness test of base material layer and surface treatment layer of isolation film

[0130] An ion polisher (model IB-19530CP) was used to ionize argon gas with an ion source. After acceleration and focusing, the isolation film cross section was polished. Then, a scanning electron microscope was used to observe the thickness of the isolation film and the surface coating perpendicular to the polished surface.

[0131] Lithium-ion battery thickness change rate and cycle performance testing

[0132] Place the lithium-ion battery in the embodiment and comparative example in a 45°C constant temperature box and let it stand for 30 minutes. Then charge the lithium-ion battery at a constant current of 1.0C to a voltage of 4.2V, then charge at a constant voltage of 4.2V to a current of 0.05C, and then discharge at a constant current of 4C to a voltage of 2.8V. This is a charge and discharge cycle. Perform the charge and discharge cycle 600 times according to the above process. Record the first discharge capacity and the discharge capacity after 600 cycles as C1 and C2 respectively. 600 , and the cycle capacity retention rate is calculated using the following formula: (C 600 / C1)×100%, which is the high temperature cycle capacity retention rate.

[0133] At the same time, the initial thickness of the lithium ion battery in the embodiment and the comparative example was measured by a micrometer as η1, and the thickness of the lithium ion battery in the embodiment and the comparative example after 600 charge and discharge cycles was measured by a micrometer as η2. The thickness change rate of the lithium ion battery was calculated using the following formula: (η2 / η1)×100%.

[0134] The test method for the capacity retention rate of normal temperature cycles is the same as that for the capacity retention rate of high temperature cycles, except that the temperature is 25°C.

[0135] Interval Cycle (ITC) Test of Lithium-ion Batteries

[0136] The lithium-ion batteries in the examples and comparative examples were placed in a 45°C thermostat and left to stand for 30 minutes. The lithium-ion batteries were then discharged to 3.0V at a current of 0.5C, and then charged to 4.2V at a current of 1C and left to stand for 24 hours. This was a charge-discharge cycle. The charge-discharge cycle was repeated 100 times according to the above process. The first discharge capacity and the discharge capacity after 100 cycles were recorded as C0 and C1 respectively. 100 , and the cycle capacity retention rate is calculated using the following formula: (C 100 / C0)×100%.

[0137] At the same time, the initial thickness of the lithium ion battery in the embodiment and the comparative example was measured by a micrometer as η1, and the thickness of the lithium ion battery in the embodiment and the comparative example after 100 charge and discharge cycles was measured by a micrometer as η3. The thickness change rate of the lithium ion battery was calculated using the following formula: (η3 / η1)×100%.

[0138] Discharge capacity retention rate of lithium-ion batteries

[0139] Place the lithium-ion battery in a high and low temperature box, first adjust to 25°C, let it stand for 30 minutes, then charge the lithium-ion battery to 4.2V at 0.5C, then charge it at constant voltage to 0.02C, let it stand for 10 minutes, then discharge it to 3.0V at 0.5C, record the discharge capacity as D0, then charge it to 4.2V at 0.5C, charge it at constant voltage to 0.02C, adjust the temperature of the high and low temperature box to -20°C, let it stand for 30 minutes, discharge it to 3.0V at 0.5C, record the capacity as D1. Discharge capacity retention rate = D1 / D0×100%

[0140] The specific implementation methods provided by the present application will be described in detail below.

[0141] Examples 1-1 to 1-33 and Comparative Examples 1-1 to 1-3

[0142] The positive electrode active material used in the examples and comparative examples in Table 1 is Li(Ni 0.8 Co 0.1 Mn0.1 )A c O2, wherein the subscript c of the A element is determined based on the content of the A element. In addition, the positive electrode active materials used in the examples and comparative examples in Table 1 all include first particles with a circularity of not less than 0.4 and second particles with a circularity of less than 0.4.

[0143] Among them, in Examples 1-1 to 1-33 and Comparative Examples 1-1 to 1-3, the cross-section of the positive electrode perpendicular to the current collector was analyzed by scanning electron microscopy. Based on the total area of ​​the positive electrode cross-section, the total cross-sectional area of ​​the first particles accounted for 22.4%, while the total cross-sectional area of ​​the second particles accounted for 44.3%.

[0144] Table 1

[0145]

[0146]

[0147]

[0148] Note 1: The content of element A in Table 1 refers to the total mass of element A added to the battery, in g; the amount of the compound of formula I in Table 1 refers to the mass of the compound of formula I added to the battery, in g.

[0149] Compared with Comparative Examples 1-1 to 1-3, Examples 1-1 to 1-9 doped Al and Zr elements in the positive electrode active material, while Example 1-10 doped Al and Ti elements in the positive electrode active material, and at the same time added the compound of formula (I-8) to the electrolyte, and the mass ratio of the doped element to the compound of formula (I-8) was in the range of 1:0.2-1:50. Referring to the electrochemical data, whether it is a conventional high temperature cycle test or an ITC test, compared with Comparative Examples 1-1 to 1-3, the electrochemical devices of Examples 1-1 to 1-10 have better cycle stability, and the thickness change of the battery before and after the cycle is smaller (indicating a lower gas production degree). This fully demonstrates that the doped elements in the positive electrode active material and the molecules of structural formula I in the electrolyte can interact with each other, forming an effective protective film on the surface of the positive electrode active material particles, reducing the side reactions between the positive electrode active material particles and the electrolyte, and improving the cycle stability of the electrochemical device.

[0150] Compared with Example 1-6, Examples 1-11 to 1-16 further add a certain amount of LiPO2F2 to the electrolyte. Referring to the electrochemical data, compared with Example 1-6, the electrochemical devices of Examples 1-11 to 1-16 exhibit better cycle stability and lower gas production. Similarly, Examples 1-27 to 1-29 correspond to Example 1-23, and the improvement is that a certain amount of LiPO2F2 is further added to the electrolyte; based on the electrochemical data, compared with Example 1-23, the electrochemical performance of the electrochemical devices of Examples 1-27 to 1-29 is better. This is because the addition of LiPO2F2 can effectively form a protective layer on the surface of the positive and negative electrodes, and can reduce impedance, which is conducive to ion transport.

[0151] In Example 1-17, the compound of formula (I-8) in the electrolyte is replaced by the compound of formula (I-3), and the electrolytes of Examples 1-18 to 126 simultaneously contain a mixture of one of the compounds of formula (I-1) to (I-3) and the compound of formula (I-8). Referring to the electrochemical data, it can be seen that, from an overall level, the electrochemical performance of the electrochemical devices of Examples 1-17 to 1-26 is substantially the same as that of the electrochemical devices of Examples 1-1 to 1-10. However, the advantage of Examples 1-17 to 1-26 is that the dosage of the compound of formula (I-8) can be reduced, and therefore, it has important commercial application value.

[0152] In Examples 1-30 to 1-33, other elements are doped into the positive electrode active material. Referring to the electrochemical data, it can be seen that the electrochemical devices of Examples 1-30 to 1-33 can all exhibit excellent cycle stability and have a low gas generation level.

[0153] Example 2-1 to Example 2-11

[0154] Embodiment 2-1 to embodiment 2-11 correspond to embodiment 1-6, and the improvement is that the compound of formula II is further added to the electrolyte. Referring to the electrochemical data, compared with embodiment 1-6, the cycle stability of the electrochemical device of embodiment 2-1 to embodiment 2-5 at room temperature is slightly reduced, but its discharge performance at low temperature has been further improved. Referring to the data of embodiment 2-6 to embodiment 2-8, by using a mixture of formula (I-8) and formula (I-3) in the electrolyte of the electrochemical device, the cycle stability and low-temperature discharge performance of the electrochemical device are improved compared with embodiment 1-6. Further, referring to the data of embodiment 2-9 to embodiment 2-11, by further adding LiPO2F2 to the electrolyte, the electrochemical performance of the electrochemical device can be further improved. This shows that the addition of the compound of formula II can further improve the low-temperature discharge performance and room-temperature cycle performance of the electrochemical device. On this basis, the combination of the compound of formula I and LiPO2F2 can effectively improve the cycle performance of the electrochemical device, and at the same time, the impedance can be reduced, thereby further improving the discharge capacity retention rate.

[0155] Table 2

[0156]

[0157]

[0158] Example 3-1 to Example 3-11

[0159] The difference between Example 3-9 and Example 1-19 is that a first additive is further added to the electrolyte of Example 3-9. Compared with Example 1-19, the electrochemical device of Example 3-9 exhibits better cycle stability and lower gas production. Example 3-1 to Example 3-8 and Example 3-10 to Example 3-11 involve adding a first additive and / or a second additive and a combination of a compound of Formula II to the electrolyte at the same time. Referring to the electrochemical data, it can be seen that the electrochemical devices corresponding to these embodiments can all exhibit excellent electrochemical performance, especially excellent cycle stability and low gas production. This is mainly due to the fact that the oxidation potential of the first additive and / or the second additive is lower than that of the compound of Formula I and the reduction potential is higher than that of the compound of Formula I, which can form a protective layer on the electrode surface in preference to the compound of Formula I, reducing the occurrence of side reactions and ensuring the interface stability during the cycle.

[0160] Table 3

[0161]

[0162]

[0163] Examples 4-1 to 4-14 and Comparative Examples 4-1 to 4-2

[0164] The examples in Table 4-1 add different elements A to different positive electrode active materials, and the molecular formula of the positive electrode active material before doping, the type and content of element A, and the proportion of the first particle and the second particle in the positive electrode active material layer are shown in Table 4-1. Compared with Comparative Example 4-1, Examples 4-1 and 4-2 have LiNi in the positive electrode active material. 0.6 Co 0.2 Mn 0.2 O2 is doped with elements. By comparing the electrochemical data, it can be seen that by doping the elements in the positive electrode active material and adding the compound of formula (I) to the electrolyte, and adjusting the mass ratio of the doped element to the compound of formula (I) within the range of 1:0.2-1:50, the particle breakage rate of the first particles in the positive electrode active material has been further reduced, and the cycle stability of the corresponding electrochemical device has been significantly improved, and the gas production degree has also been reduced. The same conclusion can be drawn by comparing Comparative Example 4-2 and Examples 4-3 to 4-5.

[0165] Examples 1-19 and Examples 4-6 to 4-10 are based on LiNi 0.8 Co 0.1 Mn 0.1 O2 is used for element doping. Referring to the electrochemical data, it can be seen that the electrochemical devices corresponding to these embodiments can all show excellent cycle performance and low gas production. In addition, appropriately reducing the proportion of the first particles in the positive electrode active material can reduce the degree of breakage of the first particles during the electrode preparation process and the charge and discharge process of the electrochemical device, and improve the cycle performance and reduce gas production.

[0166] Examples 3-3 and 4-11 to 4-14 are based on LiNi 0.8 Co 0.1 Mn 0.1 For element doping with O2, the difference between Example 3-3 and Examples 4-11 to 4-14 lies in the proportion of the total area of ​​the first particles and the proportion of the total area of ​​the second particles. From the comparison between Examples 3-3 and Examples 4-11 to 4-12 and Examples 4-13 and 4-14, it can be seen that the proportion of the first particles and the second particles within a certain range can obtain better cycle performance and reduce gas production.

[0167] Table 4-1

[0168]

[0169] Table 4-2

[0170]

[0171]

[0172] The above examples fully illustrate that whether it is doping elements in the lithium cobalt oxide (LiCoO2) system or in the ternary material (LiNi 0.6 Co 0.2 Mn 0.2 O2 and LiNi 0.8 Co 0.1 Mn 0.1 O2) is doped with elements, and the doped positive electrode active material can interact with the molecules of structural formula I in the electrolyte, ensuring the high life and low gas generation level of the electrochemical device during the entire use process.

[0173] In addition, by using a mixture of first particles and second particles in the positive electrode active material, the second particles can effectively alleviate the breakage of the first particles, reduce the side reactions between the positive electrode active material particles and the electrolyte, and improve the cycle stability of the electrochemical device.

[0174] References to "some embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner.

[0175] Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments should not be construed as limitations on the present application, and that changes, substitutions and modifications may be made to the embodiments without departing from the spirit, principles and scope of the present application.

Claims

1. An electrochemical device comprising: positive electrode; negative electrode; a separator between the positive electrode and the negative electrode; as well as Electrolyte; The positive electrode comprises a positive electrode current collector and a positive electrode active material layer disposed on the positive electrode current collector, the positive electrode active material layer comprises a positive electrode active material, the positive electrode active material comprises element A, and the element A is selected from at least one of Al, B, Ca, Mg, Ti, Cu, Nb, Si, Zr, Y or W, wherein the electrolyte comprises at least one compound of formula (I), , Where R 11 , R 12 , R 13 , R 14 , R 15 , R 16 Each is independently selected from the group consisting of: H, F, Cl, Br, I, phenyl, substituted or unsubstituted C1-C8 hydrocarbon group, wherein the electrolyte comprises a first additive, the first additive comprising at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, adiponitrile, succinonitrile, 1,3,6-hexanetricarboxylic acid nitrile, 1,2,6-hexanetricarboxylic acid nitrile or 1,3,5-pentanetricarboxylic acid nitrile; The compound of formula (I) comprises at least one of the following: ; The electrolyte comprises at least one of the compounds of formula (I-1) to (I-7) and the compound of formula (I-8), wherein the total mass ratio of the compounds of formula (I-1) to (I-7) to the compound of formula (I-8) is greater than 2:1; The mass ratio of the element A to the compound of formula (I) in the positive electrode active material is 1:0.2 to 1:

50.

2. The electrochemical device according to claim 1, wherein the electrolyte further comprises LiPO2F2, and a mass ratio of the element A to the LiPO2F2 is 1:0.01 to 1:

20.

3. The electrochemical device according to claim 1, wherein the electrolyte further comprises a compound of formula (II), , Where R 17 is a substituted or unsubstituted C1-C8 alkyl group, p is 0 or 1, The content of the compound of formula (II) accounts for less than or equal to 20% of the total mass of the electrolyte.

4. The electrochemical device according to claim 1, wherein the content of the first additive is 0.1% to 20% of the total mass of the electrolyte.

5. The electrochemical device according to claim 1, wherein the electrolyte further comprises a second additive, the second additive comprising at least one of lithium tetrafluoroborate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethylsulfonyl imide), 4,5-dicyano-2-trifluoromethylimidazolium lithium, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate or lithium bis(oxalatoborate); and wherein the content of the second additive accounts for 0.1% to 5% of the total mass of the electrolyte.

6. The electrochemical device according to claim 1, wherein the positive electrode active material layer comprises first particles, wherein the circularity of the first particles is not less than 0.4, and the cross-sectional area of ​​the first particles is not less than 20 μm 2 , based on the total area of ​​the cross section of the positive electrode perpendicular to the positive electrode current collector, the total cross-sectional area ratio of the first particles is 10% to 50%. 7 . The electrochemical device according to claim 6 , wherein the first particles include broken particles, and the total area of ​​the broken particles is no more than 30% based on the total area of ​​the first particles.

8. The electrochemical device according to claim 1, wherein the positive electrode active material layer comprises second particles, wherein the circularity of the second particles is less than 0.4, and the cross-sectional area of ​​the second particles is less than 20 μm 2 , based on the total area of ​​the cross-section of the positive electrode perpendicular to the positive electrode current collector, the total cross-sectional area of ​​the second particles is 10% to 60%.

9. The electrochemical device according to claim 1, wherein the positive electrode active material comprises at least one of the compound of formula III or the compound of formula IV: Li n Ni 1-a-b-c Co a Mn b A c O 2-m D m (Formula III) in, 0.90≤n≤1.10, 0.05≤a≤0.3, 0.002≤b≤0.3, 0.001≤c≤0.1, 0≤m≤0.05, and 0.60<1-bc<0.95; LiCoA e O 2-f D f (Formula IV) Where 0.001≤e≤0.1, 0≤f≤0.1 Wherein D is selected from at least one of S, F, N, Cl or I. 10 . The electrochemical device according to claim 1 , wherein the separator comprises a substrate layer and a surface treatment layer, the surface treatment layer comprises inorganic ceramic particles, and a thickness ratio of the substrate layer to the surface treatment layer is 2:1 to 20:

1.

11. An electronic device comprising the electrochemical device according to any one of claims 1 to 10.

Citation Information

Patent Citations

  • Electrode for battery, manufacturing method thereof, and battery

    JP2009283353A

  • Electrolyte for lithium secondary battery, and lithium secondary battery comprising same

    WO2019017567A1